Implementasi Terapi Bermain Plastisin Terhadap Penurunan Tingkat Kecemasan Pada Anak Pre Operasi Sirkumsisi Di Klinik Rathnoe Khitan Ngawi - Sefin Rahmadani, Hanif; Novitasari, Dwi; Hikmanti, Arlyana (Yayasan Inspirasi El Burhani, 2024)
Introduction: There are both religious and medical reasons for performing circumcision. There are many different approaches to circumcision, but it is still one of the most commonly performed surgical procedures worldwide. Children often experience significant levels of apprehension, fear, and pain before the circumcision procedure. Negative consequences, such as uncooperative circumcision, result from uncontrollable anxiety reactions. Objective: Using plasticine play therapy, this community service project aims to reduce anxiety in adolescent patients who will undergo circumcision surgery. This volunteer activity was conducted at Rathnoe Khitan Ngawi Clinic. Method: Implementing a hands-on plasticine play therapy method, followed by discussion and assessment, was the strategy used. Before and after receiving plasticine play therapy, the children's anxiety levels were assessed. Children at Rathnoe Khitan Ngawi Clinic who were waiting to be circumcised were the beneficiaries of this community service activity. Result: The results of this PkM are the anxiety level of the participants before the implementation of plasticine play therapy, the majority of participants felt moderate anxiety as many as 17 participants (85%), and after the implementation of plasticine play therapy there was a decrease in the anxiety scale to mild as many as 17 participants (85%). Conclusion: Based on the Wilcoxon test, the p-value is 0.001, which means that the p-value <0.05, it is concluded that there is an effect of pre and post implementation of play platisin therapy on reducing anxiety levels in children pre-circumcision surgery at the Rathnoe Khitan Ngawi Clinic.